Analisis Kualitas Produk Oilpump Menggunakan Metode Basic Seventools Dalam Upaya Meminimalisir Produk Cacat di PT. Jaya Prakarsa - Dian Putri Aulia; Wahyudin Wahyudin (Jurnal Ilmiah Wahana Pendidikan, 2022)
Currently competition in the industrial world is unpredictable, company actors always prioritize quality and always strive for the best service and product results from the production of their respective companies, this is because the customer is always generous to the company. In addition, there are many aspects that are factors for business competition in the industrial world, one aspect of which is quality. PT. Jaya Prakarsa is a company engaged in the manufacturing industry where this company produces all packaging needs, the type of production that is Made By Order causes many products to have defects. This can affect and make PT. Jaya Prakarsa experienced a decline in quality in terms of products and in terms of production. Therefore, this study aims to analyze the quality of one of the products that dominates the product defect, namely the oilpump, using the basic seventools method, where the result of this method is to minimize defects in this oilpump product. The suggestions for improvement that can be given for each problem that causes product rejects are to provide stitching results standards and boundary jigs on the stitching machine for stitching defects, and labeling pallets on semifinished and finished products.